2019
DOI: 10.1002/jclp.22873
|View full text |Cite
|
Sign up to set email alerts
|

Parenting practices among parents of children with attention‐deficit/hyperactivity disorder: Gender‐related differences

Abstract: Objective Further research is needed on parenting practices among parents of children with attention‐deficit/hyperactivity disorder (ADHD), as these practices impact children's development and outcomes. This study analyzes these practices, distinguishing between parents’ and children's gender. Method Parental warmth (affection–communication and criticism–rejection responses) and control (inductive, strict, and indulgent discipline styles) were assessed in both parents of 81 children diagnosed with ADHD (aged 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 22 publications
0
5
2
Order By: Relevance
“…However, the analysis of the results did not confirm this hypothesis, indicating that family functioning style is not a predictor of executive functioning. Considering previous reports suggesting that the family climate in which children with ADHD are raised has a significant impact on the demonstration of clinical symptoms (Barkley, 2015;Keown, 2012;Muñoz-Suazo et al, 2020;Salari et al, 2017), the results of this study seem surprising. It might seem that if there is a significant relationship between parental behavior (i.e., parental insensitivity to the needs of a child with ADHD and a positive attitude toward them), intrusive behavior, or an insecure attachment style, the opposite behavior, which is high-quality communication and satisfaction with family life, will constitute a protective factor for the cognitive functioning quality of a child with ADHD, which is one of the pivotal symptoms of this disorder.…”
Section: Family Functioning Style Within Families Raising Children Wi...contrasting
confidence: 80%
See 2 more Smart Citations
“…However, the analysis of the results did not confirm this hypothesis, indicating that family functioning style is not a predictor of executive functioning. Considering previous reports suggesting that the family climate in which children with ADHD are raised has a significant impact on the demonstration of clinical symptoms (Barkley, 2015;Keown, 2012;Muñoz-Suazo et al, 2020;Salari et al, 2017), the results of this study seem surprising. It might seem that if there is a significant relationship between parental behavior (i.e., parental insensitivity to the needs of a child with ADHD and a positive attitude toward them), intrusive behavior, or an insecure attachment style, the opposite behavior, which is high-quality communication and satisfaction with family life, will constitute a protective factor for the cognitive functioning quality of a child with ADHD, which is one of the pivotal symptoms of this disorder.…”
Section: Family Functioning Style Within Families Raising Children Wi...contrasting
confidence: 80%
“…Moreover, during childhood and adolescence, the environment begins to promote stereotypical behaviors consistent with the child’s sex, which significantly influences the parenting strategies. With regard to the relationship between the sex of a child with ADHD and the parenting style, the literature so far has been quite consistent: compared to families raising girls, those raising boys are characterized by a more authoritative style of upbringing ( Muñoz-Suazo et al, 2020 ). However, there have also been reports of the opposite direction of dependence, in which parents of girls used authoritative strategies more often ( Muñoz-Suazo et al, 2020 ).…”
Section: Family Disturbances In Adhdmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, while the composition of our sample reflected the general youth offender population, we suspect gendered effects of parenting on offending likely exist. Studies have found that in some families, parental warmth as well as discipline styles varying based on gender of the child (see for example Munoz-Suazo, Navarro-Munoz, et al (2020). We strongly encourage researchers to consider these factors in future research endeavors.…”
Section: Discussionmentioning
confidence: 91%
“…For example, while the composition of our sample reflected the general youth offender population, we suspect gendered effects of parenting on offending likely exist. Studies have found that in some families, parental warmth as well as discipline styles varying based on gender of the child (see for example Munoz‐Suazo et al (2020). We strongly encourage researchers to consider these factors in future research endeavors.…”
Section: Discussionmentioning
confidence: 99%